Identification of crab (Portunus pelagicus) using field-based DNA extraction method and isothermal amplification: Identification of crab (Portunus pelagicus) using field-based DNA extraction method and isothermal amplification - Abdullah, Asadatun; Rianti, Puji; Yani, Sri Widy; Sauqi, Sabila Diana Ahmad; Dianty Dwi Nandita; Ananda, Mutiara Fajar; Lisnaina, Evira (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
High crab production encourages the implementation of strict standards for raw materials in canned crab products, particularly regarding labeling errors (i.e., mislabeling). DNA-based identification methods are accurate for species authentication; however, their application in the field remains limited because of laboratory equipment requirements. Therefore, the development of an on-site DNA-based analytical method is essential. This study aimed to design specific primers for Portunus pelagicus using the cytochrome c oxidase subunit I (COI) gene marker and to optimize the amplification time and temperature using the colorimetric loop-mediated isothermal amplification (LAMP) method with DNA isolates obtained from field-based extraction methods. The samples included fresh crabs, canned crab products, and non-target species (Charybdis feriata, Scylla serrata, and Podophthalmus vigil). The methods comprised target species confirmation, primer design and evaluation, and in vitro testing of the P. pelagicus primer set. Primer design resulted in a COI primer set within ideal parameter ranges and high specificity to P. pelagicus based on in-silico analysis. In vitro assays demonstrated that the primers successfully detected P. pelagicus DNA in both fresh and processed samples, with an optimal reaction time of 40–60 min at 65 °C. DNA isolates obtained using dipstick and direct lysis methods were also successfully amplified, indicating that these simple extraction techniques can be applied for on-site detection without loss of sensitivity. These findings demonstrate that the developed primer set is specific to P. pelagicus and that the optimized LAMP method has strong potential as a rapid and portable authentication system for crab raw materials in the field.